Genetic and genomic evaluation for resistance to white spot syndrome virus in post-larvae of Pacific white shrimp (Litopenaeus vannamei) - Campos-Montes, Gabriel R. (2023)
The objective of the present study was to compare genetic evaluations with pedigree- and genomic-based for the time of death of post-inoculation (TD) and survival considered as a binary variable (1 = survivor, 0 = dead) (BS) to white spot syndrome obtained in a controlled experimental challenge. In seven tanks were seed a total 6132 shrimps, of which the genotypes of 1685 were obtained using a commercial 50 K SNP panel. A total of 176 families were formed from a Sire: Dam ratio of 1:2. In the challenge test, the organisms were inoculated per os with macerated shrimp tissue with a viral load of 1 × 106 copies/g of tissue. The inoculum was supplied in two doses (first of 6% and second of 4% of the biomass in each tank) whit 12 h of difference. Four approaches were used for estimating variance components and calculating genetic or genomic estimated breeding values: 1) PBLUP-1 is an animal model fitted using a pedigree-based kinship matrix using only parent-progeny relationships from individuals from the latest generation; 2) PBLUP-All is the same as above but using the genealogy from 19 generations; 3) GBLUP is an animal model fitted using a genomic-based relationship matrix including genotyped animals only, and 4) ssGBLUP is an animal model fitted using a blend between the pedigree and genomic relationship matrix. The heritability values obtained for TD and BS with the four approaches ranged from 0.072 to 0.105 and 0.069 to 0.095, respectively. The heritability estimators obtained with genomic information were slightly higher than those obtained with only pedigree information. PBLUP-All and ssGBLUP present proportionally lower standard errors than PBLUP-1 and GBLUP. The use of genomic information (GBLUP and ssGBLUP) increased the mean accuracy of estimated breeding values by an average of 38% and 54% concerning methods that only used phenotypic information (PBLUP-1 and PBLUP-ALL). Using a 50 K SNP genotyping panel and deep pedigree information increased heritability estimation of traits associated with resistance to white spot syndrome virus in Pacific white shrimp. Using genomic information substantially improves the accuracy of estimated breeding values when using ssGBLUP compared to pedigree-based methods. Genomic selection will allow individual selection within-family by predicting the genetic values of animals not exposed to the white spot syndrome virus.